Analytical Criticism of Some Select Poems of Poet Arun Das (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
Some select poems of poet Arun Das are the new platforms in Bengali Poetry. His philosophy on the matter is the “Sudarshan Chakra” at Puri temple. His psychology to matter to give a stir to subconscious mind is a unique pleasure as his psychology only helps the mind to reach ‘supreme consciousness’ by overcoming unconsciousness consciousness, subconsciousness of the mind. His way of reaching the ‘supreme consciousness’, is a new platform to society. He meditates on the matter. Without concentrating the feeling, willing and thinking i. e. spirits of spirituality, the poet will never reach the goal of mind, as the layers of the mind are components to each other. No layer of mind is rejected, but they are added or deducted in the analysis of “Brahma”. His poems mainly give us a new taste to calculate the “Brahma” from z-way by using all components of poetry. His love for beauty of women and nature makes him Arjun of poetry to calculate in a subtle way the “Brahma” of “Z-generation poems”. His poems are the eco-friends in postcolonial ecology. He always wants to be a migratory bird. His theory of poetry ‘Letter is Brahma’ is a new taste in postmodern Bengali poetry. The Knowledge of the select poems is free to choose the meaning of “Brahma” to create a new one and to give the sublime happiness to the rejected heart. The words of the select poems are common but the presentation of the poems is the way to enjoy everything from the very subtle “supreme consciousness” of the mind. He is the pioneer of poetry of “supreme consciousness” of the mind in Bengali literature. By writing poems Poet Arun Das gives a mind where the reader gets a new platform in thinking. His “Z-generation poems” have the soothing balm for the rejected and alienated hearts.